2013
DOI: 10.3892/ijmm.2013.1400
|View full text |Cite
|
Sign up to set email alerts
|

miR-9 functions as a tumor suppressor in ovarian serous carcinoma by targeting TLN1

Abstract: microRNAs (miRNAs) are important regulators of gene expression during tumorigenesis. The downregulation of microRNA-9 (miR-9) has been reported in ovarian serous carcinoma (OSC), indicating a role for miR-9 in this type of cancer. In this study, we investigated the biological significance of miR-9 in OSC in vitro. Using 3 OSC cell lines, SKOV3, CAOV3 and OVCAR3, which underexpresss miR-9, we demonstrate that the exogenous miR-9 transfection inhibits OSC cell proliferation, migration and invasion. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Overexpression of talin occurs in several solid tumors, including PCa, 4 oral squamous cell carcinoma 5 and ovarian serous carcinoma, 6 with overexpression correlating with higher tumor grade and metastasis. 4-6 In these studies, phosphorylation of talin was not examined; therefore overexpression and phosphorylation may not be mutually exclusive mechanisms for β1 integrin activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of talin occurs in several solid tumors, including PCa, 4 oral squamous cell carcinoma 5 and ovarian serous carcinoma, 6 with overexpression correlating with higher tumor grade and metastasis. 4-6 In these studies, phosphorylation of talin was not examined; therefore overexpression and phosphorylation may not be mutually exclusive mechanisms for β1 integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…2 While numerous alterations in both tumor cells and the tumor microenvironment are required for metastasis of solid tumors, 3 recent studies have implicated aberrant expression of talin in promoting such critical steps in metastasis as adhesion, migration, invasion, cellular survival and proliferation. 4-6 …”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2009) reported that miR-9 inhibited ovarian cancer cell growth by regulating nuclear factor kappa B1 (NF-κB1) expression. However, Tang et al (2013) reported that miR-9 might act through the suppression of the talin 1/FAK/Akt pathway. miR-9 has also been demonstrated to improve the chemotherapeutic efficacy against ovarian cancer, as targeted inhibition of miR-9 sensitizes ovarian xenograft tumors to cisplatin and PARP inhibitor (Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that miR-9 mediates the suppression of Akt/FOXO1 axis by curcumin in ovarian cancer cells. Indeed, the inactivation of Akt signaling by miR-9 is also described in a previous study (Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…A recent study has shown that miR-9 has the potential of improving chemotherapeutic efficacy in ovarian cancer, as targeted inhibition of miR-9 sensitizes ovarian xenograft tumors to cisplatin and PARP inhibitor . Tang et al (2013) reported that miR-9 inhibits ovarian cancer cell proliferation, migration, and invasion through suppression of talin 1/FAK/Akt pathway. These studies combined with the finding that curcumin can alter miRNA expression profiles in cancer cells (Sun et al, 2008) suggest the possibility that miR-9 may be involved in the anticancer effects of curcumin against ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%